Blending in or standing out? The disclosure dilemma of ad cues of social media native advertising - Maike Hübner; Maike Hübner; Julia Thalmann; Jörg Henseler; Jörg Henseler (Frontiers in Psychology)
IntroductionAs social media platforms increasingly rely on native advertising embedded within user feeds, an open question is whether sponsored posts garner comparable, greater, or reduced attention relative to surrounding non-sponsored content. Subtle cues (e.g., disclosures, call-to-action (CTA) buttons) may alert users to the commercial nature of these posts or remain unnoticed in rapid-scroll environments. In this study, we aimed to disentangle the dynamics of the “disclosure dilemma” in native advertising, examining whether ad cues blend into the content flow unnoticed or stand out and prompt rapid disengagement.MethodsThis study adopted a mixed-methods design with 152 participants randomly assigned to one of three mock-up Instagram feeds containing both sponsored and organic posts. Eye-tracking measured visual attention (dwell time, fixation counts), while cued-retrospective think-aloud (CRTA) interviews probed underlying user rationales for focusing on or overlooking specific content.ResultsSponsored posts received significantly less dwell time and fewer fixations than their organic counterparts, indicating persistent ad avoidance despite a native design. Moreover, early fixation on disclosures or CTA elements in sponsored posts often triggered an immediate decline in further engagement, functioning as “flags” that activate learned avoidance. CRTA data revealed divergent user interpretations: some participants felt misled by the subtlety of sponsored posts, whereas others remained unaware of disclosures until late in their viewing.DiscussionThese findings point to an evolving form of “native ad blindness,” shaped by rapid heuristic scanning and schema-based recognition of minimal ad signals. Conceptually, this study refines theories of banner blindness, persuasion knowledge, and dual-process filtering, providing practical insights for advertisers seeking to balance transparency with user engagement amid competition from non-sponsored content.